(untitled) (Colombia Medica, 2010)
Objective: To determine factors associated with mortality by sepsis syndrome in children. Methods: We performed an analytical study of cases and controls, which included patients between 31 days and 14 years of age, treated at Hospital Universitario del Valle in Cali, Colombia, with sepsis syndrome between 1999 and 2003. Information was gathered from medical records and books. The outcome variable was the status on discharge from hospital (alive or dead). All the dead children were verified in the hospital records and all the living children were confirmed alive four weeks after discharge. The exposure control variables were age, gender, origin, socioeconomic status, educational level of mothers, family order of the child, classification and origin of sepsis, nutritional status, underlying disease, presence and type of immunosuppression, invasive procedures, duration of surgery, broad-spectrum antibiotics, as well as preoperative, hospital and intensive care stay. Results: We evaluated 110 cases and 110 controls, 79 with diagnosis of sepsis and 31 with septic shock. The cases had more days of evolution of the disease, higher proportion of family order of the child between third and fifth offspring, malnutrition, acquired immunosuppression, respiratory origin of sepsis, and shorter hospital stay and in intensive care. The logistic regression model showed that more days of disease progression (OR 1.05 CI 95% 1.01-1.10), and family order of the child (1.39 CI 95% 1.11-1.74), meant greater risk of dying from sepsis syndrome. Conclusions: It must be insisted to the community of the importance of consultation and early diagnosis of any infectious process for rapid identification of the bacteria, allowing the introduction of specific treatment and referral according to severity level.